2012
DOI: 10.2460/javma.240.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical site infection rates in clean and clean-contaminated wounds in dogs and cats after minimally invasive versus open surgery: 179 cases (2007–2008)

Abstract: MIS may be associated with a lower SSI rate, compared with OS, but confounding factors such as differences in surgery time and preoperative preparation contributed in part to this finding. As such, surgical approach cannot be categorized as an independent risk factor for SSIs in small animals until further studies are performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
1
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 39 publications
(85 reference statements)
4
105
1
4
Order By: Relevance
“…[11][12][13] The potential advantages of laparoscopic-assisted surgical procedures include smaller incisions, decreased soft-tissue trauma, decreased postoperative pain, decreased hospitalization time, and greater visualization compared with conventional surgeries. [11][12][13][14][15][16]17 Similarly, reducing port size and number, a concept that has gained popularity in human medicine, is now progressing in veterinary minimally invasive surgery. [13][14][15][17][18][19] To that end, specially designed single-incision devices, such as the SILS port, have allowed the use of multiple instruments through a single port and have helped to facilitate surgical advances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] The potential advantages of laparoscopic-assisted surgical procedures include smaller incisions, decreased soft-tissue trauma, decreased postoperative pain, decreased hospitalization time, and greater visualization compared with conventional surgeries. [11][12][13][14][15][16]17 Similarly, reducing port size and number, a concept that has gained popularity in human medicine, is now progressing in veterinary minimally invasive surgery. [13][14][15][17][18][19] To that end, specially designed single-incision devices, such as the SILS port, have allowed the use of multiple instruments through a single port and have helped to facilitate surgical advances.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that minimally invasive procedures may reduce postoperative infection rates compared to conventional techniques. 16 Whether or not this is the case for laparoscopic-assisted intestinal procedures remains to be answered but is worth future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 Another study reported that for every 90 min of surgery time, there was a 2.1 greater odds of SSI. 13 Prolonged anesthesia has been reported as a predisposing factor for SSI. One veterinary study reported a 30% increase in the risk of SSI in clean wounds for each additional hour of anesthesia.…”
Section: Risk Factors For Development Of Ssismentioning
confidence: 99%
“…In a study comparing surgical site infection (SSI) rates between open and minimally invasive surgery, on univariate analysis surgical approach (MIS versus open) was found to have a beneficial effect on SSI rate post‐operatively (Mayhew et al . ). The SSI rate for the open group was 5.5% compared to an SSI rate of 1.7% in the MIS group.…”
Section: Introductionmentioning
confidence: 97%